2014
DOI: 10.1063/1.4886535
|View full text |Cite
|
Sign up to set email alerts
|

Spectra of discrete Schrödinger operators with primitive invertible substitution potentials

Abstract: We study the spectral properties of discrete Schrödinger operators with potentials given by primitive invertible substitution sequences (or by Sturmian sequences whose rotation angle has an eventually periodic continued fraction expansion, a strictly larger class than primitive invertible substitution sequences). It is known that operators from this family have spectra which are Cantor sets of zero Lebesgue measure. We show that the Hausdorff dimension of this set tends to 1 as coupling constant λ tends to 0. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 49 publications
0
37
0
Order By: Relevance
“…The dimensional properties of its DOS have been studied in many works, see for example [28,6,7,8,26], especially the recent work [9]. We summarize the results which are related to our paper as follows: N α 1 ,λ is exact-dimensional and Girand [12] and Mei [23] considered the frequency α with eventually periodic continued fraction expansion. In both papers they showed that lim λ→0 d(α, λ) = 1 and N α,λ is exact dimensional for small λ.…”
Section: Introductionmentioning
confidence: 85%
“…The dimensional properties of its DOS have been studied in many works, see for example [28,6,7,8,26], especially the recent work [9]. We summarize the results which are related to our paper as follows: N α 1 ,λ is exact-dimensional and Girand [12] and Mei [23] considered the frequency α with eventually periodic continued fraction expansion. In both papers they showed that lim λ→0 d(α, λ) = 1 and N α,λ is exact dimensional for small λ.…”
Section: Introductionmentioning
confidence: 85%
“…log ∂k Notice that Lemma 3.5 implies also that for come constantĈ > 0 we have Therefore one can choose smallness of the C 2 norms of {g i } i=1,...,m in (8) so that for some δ * > 0 and all large enough values of n ∈ N we have d dλ φ ω,τ (λ) ≥ nδ * n s=1 l (s) (26) for any ω, τ ∈ Ω with |ω ∧ τ | = n. In particular, if ω, τ ∈ Ω 1 then (26) together with (19) imply that d dλ φ ω,τ (λ) ≥ nδ * m −βn = nδ * m −β|ω∧τ | , which implies (20) and hence verifies the assumption (13). Finally, the Shannon-McMillan-Breiman Theorem implies that…”
Section: Proofsmentioning
confidence: 99%
“…Theorem 2.2 ([2], see also Theorem 4.1 from [26]). The set Λ λ is a compact locally maximal T s -invariant transitive hyperbolic subset of S λ , and the periodic points of T s form a dense subset of Λ λ .…”
Section: Metallic Mean Sequencementioning
confidence: 99%